2010
DOI: 10.4069/kjwhn.2010.16.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health Locus of Control, Depression, Wellbeing, and Health Promoting Lifestyle Profile II in Middle Aged Korean and Korean-American Women

Abstract: W-city, Korea, were collected using a self administered questionnaire including items on HLOC, HPLP, a Wellbeing Index and Major Depression Inventory. Results: There were statistically significant differences between the middle aged Koreans and Korean-Americans on mean age, education, religion, and current health insurance. Significant differences were found on HLOC (F= 2.504, p=.033) and Wellbeing (F=2.451, p=.036). The results also showed significant differences on HPLP (total HPLP, F=4.655, p=.001; physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A number of factors, including health literacy, may contribute to poor health outcomes of Korean immigrants. Consistent with previous studies (Lee et al 2010a,b, Song et al 2010, our findings suggest that a lack of health insurance and English proficiency are main barriers to utilisation of healthcare services. Past research has shown that between 46% and 55% of Koreans have health insurance coverage, the lowest rate among all racial and ethnic groups in the United States (Yoo & Kim 2008).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A number of factors, including health literacy, may contribute to poor health outcomes of Korean immigrants. Consistent with previous studies (Lee et al 2010a,b, Song et al 2010, our findings suggest that a lack of health insurance and English proficiency are main barriers to utilisation of healthcare services. Past research has shown that between 46% and 55% of Koreans have health insurance coverage, the lowest rate among all racial and ethnic groups in the United States (Yoo & Kim 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the results of Lee et al . (,b); in their study, 91.3% of the middle‐aged Korean American women reported going to church not only for religious purposes but also for social networking. Our study also indicates that Korean churches have become a place for community members to obtain health information and education.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations